The Effect of Annealing on the Structural and Optical Properties of Titanium Dioxide Films Deposited by Electron Beam Assisted PVD - Yaser M. Abdulraheem; Sahar Ghoraishi; Lidia Arockia-Thai; Suji K. Zachariah; Moustafa Ghannam (Advances in Materials Science and Engineering)
Titanium dioxide thin films were deposited on crystalline silicon substrates by electron beam physical vapor deposition. The deposition was performed under vacuum ranging from 10−5 to 10−6 Torr without process gases, resulting in homogeneous TiO2-x layers with a thickness of around 100 nm. Samples were then annealed at high temperatures ranging from 500°C to 800°C for 4 hours under nitrogen, and their structural and optical properties along with their chemical structure were characterized before and after annealing. The chemical and structural characterization revealed a substoichiometric TiO2-x film with oxygen vacancies, voids, and an interface oxide layer. It was found from X-ray diffraction that the deposited films were amorphous and crystallization to anatase phase occurred for annealed samples and was more pronounced for annealing temperatures above 700°C. The refractive index obtained through spectroscopic ellipsometry ranged between 2.09 and 2.37 in the wavelength range, 900 nm to 400 nm for the as-deposited sample, and jumped to the range between 2.23 and 2.65 for samples annealed at 800°C. The minimum surface reflectance changed from around 0.6% for the as-deposited samples to 2.5% for the samples annealed at 800°C.